Il valore sociale dei rifiuti. L’intreccio tra istituzioni e pratiche di recupero nello spazio urbano di Casablanca (Marocco) - Anna Karin Giannotta (Archivio Antropologico Mediterraneo)
This paper illustrates the findings of an ethnographic research conducted in Casablanca (Morocco) between 2016 and 2017. The aim is to shed light on waste circulation between the main social actors of the analysed cultural scenario: informal waste-pickers, wholesalers and institutions. By de-constructing the garbage collectors’ single-narration, I will propose a fluid description of their agency, in a constant tension with the institutions that dominate waste-governance processes. The focus on the socio-material interactions will lead me towards a repositioning on the very notions of informality and waste, both interpreted as driving resources of sharing processes between people, places and objects, in a local scenario where the complementarity between official and unofficial practices will stand out.